The Application Of Problem-Based Learning (Pbl) Learning Model To Improve The Activeness And Learning Outcomes Of 7th Grade Students In Ips Subjects At Smp Negeri 7 Kota Bengkulu - Anisa Lestari; Bahrin, Bahrin; Herwan, Herwan (Universitas Dehasen Bengkulu, 2025)
This study aims to determine whether the application of the Problem Based Learning (PBL) learning model can improve student activity and learning outcomes in class 7g of SMP Negeri 7 Bengkulu City. This Classroom Action Research (CAR) was conducted in two cycles because it had achieved the indicators of successful action. The indicator of the success of this study is a minimum student learning activity score of 4. The subjects of this study were 32 students of class 7g of SMP Negeri 7 Bengkulu City. Data collection techniques in this study used observation, pretest scores and posttest scores. The results of the study showed that through the application of the Problem Based Learning (PBL) learning model, it can improve student learning activity and outcomes in social studies subjects. This can be seen from: 1) an increase in student learning activity. The average score of student learning activity in cycle I was 144, included in the sufficient category, and in cycle II the average score of student learning activity increased to 571.5, included in the very good category. 2) Judging from the results of the t-test at a significance level of 5% and degrees of freedom of 31, it shows that t count = 16.53 ≥ t table 1.696, meaning that t table is smaller than t count, meaning that there is a significant increase, namely that cycle II is better than cycle.